Is vaping cessation like smoking cessation? A qualitative study exploring the responses of youth and young adults who vape e-cigarettes. (February 2021) - Sanchez, Sherald; Kaufman, Pamela; Pelletier, Hayley; Baskerville, Bruce; Feng, Patrick; O'Connor, Shawn; Schwartz, Robert; Chaiton, Michael
Highlights: Participants identified key differences and similarities between vaping and smoking. There is low self-awareness of one's own vaping patterns and habits. Interventions designed for vaping cessation are more appropriate for youth. Abstract: Introduction: Young people are now seeking help to quit vaping. However, little is known about vaping cessation. To bridge the gap between the current state of research and the urgent need for interventions, practitioners have drawn upon smoking cessation models under the assumption that vaping and smoking are fairly similar. In this study, we sought to understand the nature and extent to which vaping is similar to smoking in order to inform the development of vaping cessation interventions for young people. Methods: Seven focus groups were conducted between November 2019 and February 2020 among youth (ages 16–18) and young adults (ages 19–29) living in the Greater Toronto Area who self-identified as e-cigarette vapers and expressed interest in vaping cessation ( n  = 41). Focus groups were audio recorded, transcribed verbatim, and analyzed using thematic analysis methods. Results: Perceived similarities between vaping and smoking emerged from participant narratives: three themes relating to barriers to quitting (social benefits, stress reduction, sensory and behavioural gratification), and three relating to reasons for quitting (financial loss, industry influence, dependence). However, there were also perceived differences that emerged: three themes relating to barriers to quitting vaping (enjoyment of flavours, convenience and discreetness, lack of self-awareness of vaping behaviours), and two relating to reasons for quitting vaping (lack of trusted information, perceived social acceptability). Conclusions: Although there is significant overlap between vaping and smoking, understanding perceived differences in barriers to quitting and reasons for quitting is critical to advancing vaping cessation research and practice among young people.